All Possible Worlds: A History of Geographical Ideas - Martin, Geoffrey J.; James, Preston E.; James, Eileen W. (Wiley & Sons, 1993)
Keywords: Geography; History; dept.egm; faculty_collection

Book Review: Smith, H.D. and Vallega, A., editors, 1991: The development of integrated sea-use management. London: Routledge. xvi + 284 pp. £45.00 cloth. ISBN: 0 415 03816 2 - Glassner, Martin Ira (Progress in Human Geography, 1993)
Keywords: book.review; dept.egm

Book Review: Review essay: Recent books on marine affairs - Glassner, Martin Ira (Ocean Development and International Law, 1993)
Keywords: book.review; dept.egm

Management of marine resources as a binding force in the Eastern Caribbean - Glassner, Martin Ira (Ocean & Coastal Management, 1993)
The history of the Commonwealth Caribbean is replete with failed attempts at various degrees of economic and political integration. The Caribbean Sea itself is rather poor in both living and non-living resources, and the entire region-land and water-is suffering from varying degrees of environmental degradation. This article suggests that regional co-operation in the management of marine resources, particularly in the Anglophone islands of the Eastern Caribbean, could serve as an 'engine of integration'-something previous attempts lacked. There is no assurance that such an effort would be successful, however, despite good intentions, co-operation in many areas at present and some real cultural affinities. The centrifugal forces at work here are still very powerful, including parochialism and the scarcity of resources other than sun, sand and sea. © 1993.
Keywords: Anglophone islands; Caribbean; Caribbean, (East); Centrifugal forces; Coastal engineering; Commonwealth Caribbean; Eastern caribbean; Engine of integration; Environmental degradation; Environmental impact; Laws and legislation; Management; Management of marine resources; Scarcity of resources; dept.egm; developing country; economic and political integration; economic association; environmental degradation; environmental resource management; marine resource management; marine resources; regional cooperation; resources management

The political geography of the sea - Glassner, Martin Ira (Canadian Geographer, 1993)
Keywords: dept.egm

Enhancing teaching excellence through a scientist-science teacher collaborative process. - Haakonsen, Harry O; Stone, A Harris; Tomala, Gail; Hageman, Susan (Journal of Science Teacher Education, 1993)
Keywords: dept.egm